Culprit Plaque Characteristics in Patients With Sleep‐Disordered Breathing Undergoing Percutaneous Coronary Intervention: An Intravascular Ultrasound Study. Issue 19 (2nd October 2018) - Wada, Hideki; Dohi, Tomotaka; Kasai, Takatoshi; Yatsu, Shoichiro; Naito, Ryo; Kato, Yoshiteru; Okai, Iwao; Iwata, Hiroshi; Isoda, Kikuo; Okazaki, Shinya; Miyauchi, Katsumi; Daida, Hiroyuki
Abstract : Background: Sleep‐disordered breathing (SDB) is a novel cardiovascular risk factor. However, the coronary plaque characteristics of patients with SDB with coronary artery disease are still unclear. Methods and Results: This study included 289 consecutive patients with coronary artery disease undergoing percutaneous coronary intervention. Plaque characteristics of the culprit lesion were assessed by preintervention intravascular ultrasound. The presence of SDB was defined as a 3% oxygen desaturation index of ≥15 events per hour measured by nocturnal pulse oximetry. Of 289 patients, the median 3% oxygen desaturation index was 9.6 (interquartile range, 5.1–16.6), and 88 patients (30.4%) were defined as having SDB. Compared with the no‐SDB group, the SDB group had a larger total atheroma volume of the culprit lesion (224.5 mm 3 versus 190.8 mm 3, P =0.05). The median maximum attenuation and calcification angle were 140° and 130°, respectively. Attenuated plaque with a maximum attenuation angle >140° was more frequently observed in the SDB group compared with the no‐SDB group (34.9% versus 22.6%; P =0.03). However, there were no statistically significant differences between groups in the maximum calcium angle and the frequency of calcific plaques with a maximum calcium angle >130°. Multivariable logistic regression analysis showed that the presence of SDB was a significant predictor of a greater ultrasound attenuation angle (>140°) (odds ratio, 1.86; 95% confidence interval, 1.02–3.39; P =0.04). Conclusions: SDB was associated with larger atheroma plaque volume and a greater ultrasound attenuation, which are discriminators of plaque vulnerability. Further studies are needed to clarify the effects of SDB treatment on coronary plaque lesions.